Implementing 802.1X security solutions for wired and wireless networks - Geier, James T. (Wiley Pub., 2008)
You know it's essential, and you've heard that it can be tricky? implementing the 802.1x standard. Here is a road map that will enable you to approach 802.1x implementation with confidence so that you can conduct successful implementation of 802.1x in both wired and wireless networks. Complete with step-by-step instructions, recommendations to help you choose the best solutions, and troubleshooting tips, it lets you benefit from the experience of others who have met the challenge.